2019
DOI: 10.1146/annurev-criminol-011518-024748
|View full text |Cite
|
Sign up to set email alerts
|

Crime Victims’ Decisions to Call the Police: Past Research and New Directions

Abstract: Over the past 50 years, researchers in the United States and abroad have debated the inherent inequities within justice systems that contribute to the underreporting of crime to the police. Our review summarizes existing knowledge about victim reporting and outlines new directions in theory and empirical research that situate this work within a broader perspective on victim help-seeking. We begin with a short review of the historical development of research on victim reporting and its implications for research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 130 publications
(236 reference statements)
2
80
0
3
Order By: Relevance
“…13 Following Black's theory, the literature has also explained that people living in places that lack informal social controls and support had difficulties in seeking formal police protection. 12 However, perceived neighborhood support was negatively associated with the intent to report in this Korean data. This result was consistent with a recent study conducted in Canada 21 in which survivors of partner violence did not feel the need to report the violence if there were police stations in their neighborhood.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…13 Following Black's theory, the literature has also explained that people living in places that lack informal social controls and support had difficulties in seeking formal police protection. 12 However, perceived neighborhood support was negatively associated with the intent to report in this Korean data. This result was consistent with a recent study conducted in Canada 21 in which survivors of partner violence did not feel the need to report the violence if there were police stations in their neighborhood.…”
Section: Discussionmentioning
confidence: 67%
“…So far, extensive research has been conducted to explain what influences people to report FV to the police. 12 In his theory of law, 13 Black described law from a more quantitative perspective. He argued that the quantity of law, including the actions of law mobilization and application (e.g., reporting), can differ, depending on the individual's characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings on the relationship between race and class and reporting have been mixed, though the majority of research finds that females are more likely than males to report (Baumer Eric ; Berg et al ; Felson et al ; Tarling and Morris ; Wolitzky‐Taylor et al ; Zavala ). Recent studies have highlighted possible reasons for reporting among marginalized groups, including lack of other alternatives (Bell ; Xie and Baumer ; Xie and Lauritsen ). This research has also found that negative attitudes toward the police can be superseded by instrumental concerns such as immediate need for help (Hagan et al ; Slocum ).…”
Section: Introductionmentioning
confidence: 99%
“…This article has broader theoretical implications for the study of victims' help-seeking decisions (Xie and Baumer 2019a). A large body of evidence demonstrates that incident-and individual-level characteristics consistently shape decisions to report crime victimization to the police (Baumer and Lauritsen 2010;Felson et al 2002;Gottfredson and Hindelang 1979;Skogan 1984;Xie and Baumer 2019a).…”
mentioning
confidence: 96%